From Struggle to Sustainability: How Latur Farmers Transformed Agriculture and Their Livelihoods in Maharashtra - Garg, Kaushal K.; Majeed, Israr; Anantha, Kanugod H.; Venkataradha, A.; Pramanik, Soumitra; Khuswaha, Dharmendra; Shinde, Amit; Singh, Ramesh; Kumar, Shalander; Jat, Mangi L. (International Crops Research Institute for the Semi-Arid Tropics, 2024)
Latur district in Maharashtra has long faced critical agricultural challenges, including erratic rainfall, groundwater depletion, acute water shortage and soil degradation. With fragmented landholdings averaging 1–2 hectares, smallholder farmers struggled to sustain agricultural productivity and profitability. Recognizing these challenges, the Groundwater Survey and Development Agency (GSDA), in collaboration with ICRISAT, launched a transformative initiative under the Atal Bhujal Yojana (2023–2025) supported by CGIAR Initiative on Sustainable Intensification of Mixed Farming Systems. About 440 farm households were involved in this initiative. To design effective interventions, a comprehensive multidimensional analysis was conducted, evaluating the economic, social, and environmental sustainability of farming systems using ICRISAT’s MSAT framework. Additionally, a Land Resource Inventory (LRI) assessment was undertaken to assess soil characteristics and land use potential, while a hydrological assessment helped identify water availability, recharge potential, and vulnerabilities. These assessments provided a strong foundation for planning targeted resource conservation and use while designing holistic solutions from farm to landscape scale for sustainable agricultural improvements. Based on these assessments and a participatory community-led approach, key entry points were identified at both the landscape scale and farming systems scale, along with market linkages to enhance sustainability.